Gibbon focused tourism as a conservation tool: the behavioural response of Skywalker hoolock gibbons (Hoolock tianxing) to tourists. Issue 2 (3rd April 2023) - Williams, Jessica L.; Behie, Alison M.; Fan, Peng-Fei
ABSTRACT : Biodiversity is declining in part due to destructive and unsustainable human activity. Nature-based tourism, informed by scientific data, has the potential to replace some income generated by unsustainable practices. We observed two groups of Hoolock tianxing gibbons – one exposed to tourists and the other to small research teams – at Gaoligong National Nature Reserve, China. We found that H. tianxing gibbons spent significantly more time scanning and less time resting in the presence of tourists, and that these effects were amplified by the number of tourists. We did not find a difference in overall daily activity budgets of individuals exposed to tourism compared to individuals exposed to research teams, suggesting that behavioural changes are currently restricted to periods when tourists are present. Gibbon-focused tourism programs have the potential to contribute to conservation efforts and our study demonstrates that programs informed by scientific research can be an ethical and sustainable conservation tool.